Amanah Dalam Pekerjaan Menurut Tafsir Al-tabari - Muhammad Yusry Affandy Md Isa (Yayasan Dakwah Islamiah Malaysia (YADIM), 2024)
Integrity is an important value in a work practice. Islam has required this value even though it involves working with fellow human beings. This article features the emphasis on trust in Islam based on eight Quranic verses and the interpretation of the Quran presented by Ibn Jarir al-Tabari. He is Abu Ja’far Muhammad ibn Jarir al-Tabari who has produced Jami’ al-Bayan ‘an Ta’wil Ay al-Qur’an, also known as Tafsir al-Tabari, which is one of the earliest interpretation work in ma’thur area. In the world of work, integrity issues often occur. Every Muslim should be aware that integrity is a principle of the Qur’an that should not be ignored. This study is important to be used as a guideline for the integrity of the individual Muslim work especially in Malaysia and subsequently to pursue a good quality of God’s work. This study applies the method of data analysis included deductive and descriptive methods which are used to obtain the verses of trust in the al-Qur’an al-Karim and describe the facts of interpretation in the work of Tafsir al-Tabari. Furthermore, the data were analyzed to obtain conclusions about the aspects of trust emphasized in the context of work practice. The findings show that although al-mat’hur’s interpretation is under the influence of classical scientific materials, the interpretation of trust is always relevant and appropriate to emphasize in the work environment over time. Islam is very obliging of the behavior of trust to succeed in work among human beings in line with the mission of implementing the trust from Allah SW.T. The most important formulation is that each sentence of the verse interpreted by al-Tabari is closely related to the working emvironment. Trust is divided into two parts, namely the trust of Allah SWT and trust among fellow human beings. In animating integrity, a Muslim should understand that Allah SWT has sent down a message of trust that must be implemented as soon as possible. This obligation can be implemented with self- adheral of positive competence in management or subordinate.